Penggunaan Cuka Bambu Sebagai Alternatif Pengendalian Penyakit Bulai pada Tanaman Jagung - Muhammad Habibullah; Danes Suhendra (Prodi. Agroteknologi dan Perkebunan, Universitas Tjut Nyak Dhien, 2020)
Introduction: Downy mildew control using pesticides has been used intensively and led to the onset of resistant strains. This research aims to find out the effect of bamboo vinegar administration on disease incidence, disease severity, disease progression, and growth of maize. Materials and Methods: This research was conducted from June to August 2020 in the laboratory and Screenhouse of the Faculty of Agriculture, Universitas Tidar. The experiment was experimentally conducted using a Completely Randomized Design (CRD) consisting of 3 treatments with 6. are plants. In each polybag used there are 3 maize so there are 54 plants tested. The treatment tested is of bamboo vinegar and maydis (negative control), of bamboo vinegar with inoculation P. maydis (positive control), application bamboo vinegar 2 ml l-1 with inoculation P. maydis. Observations on the agronomic influence of maize covering height, , and dry weight were analyzed using ANOVA at a significance of 5% followed by LSD test at the same real level using software R v. 4.0.2. Results: Bamboo vinegar showed lignification in the treatment of stronger bamboo vinegar in corn leaf tissue, did not decrease in disease incidence, but decreased the disease severity by 22.18% and decreased disease the progression by 34.74% based on AUDPC value. The growth of maize, bamboo vinegar-treated shows values are not significant negative control.